2018
DOI: 10.1111/bjet.12620
|View full text |Cite
|
Sign up to set email alerts
|

Using tablets in free play: The implementation of the digital play framework in Greece

Abstract: The use of tablets in a Greek kindergarten class (16 children aged 4–5) under the digital play framework (Bird & Edwards, 2015) is explored in this study. The Vygotskian framework was adapted with permission in the Greek language and socio‐cultural context. The aim was to understand children's use of new, touchscreen technologies, but also to identify a useful way to observe the progression of that engagement. The project lasted for 4 months and children were observed ten times (written and video recorded obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…There are different acts of contribution, of which some appear to be of greater importance in digital play activities compared to non-digital play activities. One act is to contribute by sharing knowledge, which appears to be expected based on previous studies indicating how participation in digital play foster opportunities for children to support others by sharing knowledge (Arnott, 2016;Edwards & Bird, 2017;Hatzigianni et al, 2018). Performing selves are shown to use those previous lived experiences that combine various aspects of life when making meaning in and of virtual worlds (Huh, 2017a;Maine, 2017;Marsh, 2017).…”
Section: Contributionmentioning
confidence: 72%
See 1 more Smart Citation
“…There are different acts of contribution, of which some appear to be of greater importance in digital play activities compared to non-digital play activities. One act is to contribute by sharing knowledge, which appears to be expected based on previous studies indicating how participation in digital play foster opportunities for children to support others by sharing knowledge (Arnott, 2016;Edwards & Bird, 2017;Hatzigianni et al, 2018). Performing selves are shown to use those previous lived experiences that combine various aspects of life when making meaning in and of virtual worlds (Huh, 2017a;Maine, 2017;Marsh, 2017).…”
Section: Contributionmentioning
confidence: 72%
“…The willingness to take risks and the use of trial and error strategies when exploring appears to be frequently occurring in digital play activities (Honeyford & Boyd, 2015;Wernholm, 2021). Performing selves express learning from mistakes and failures (Honeyford & Boyd, 2015;Pei Hwa, 2018) by putting reflective skills into play (Hatzigianni, Gregoriadis, Karagiorgou, & Chatzigeorgiadou, 2018;Wernholm & Reneland-Forsman, 2019) and thereby adding experiences to an elaborated understanding (Wohlwend, 2017b). It is suggested that children through productive failure and struggle understand increasingly complex matters (Maine, 2017;Wohlwend, 2017b) and co-construct knowledge (Marlatt, 2019).…”
Section: Explorationmentioning
confidence: 99%
“…Likewise, Petersen (2015) investigated children’s agency and interactions in the use of multimodal approaches, such as the use of tablets in preschools, and emphasized that understanding children’s agency may be expanded by the use of multimodal approaches. In the same line, the studies of Yelland (2018) and Hatzigianni et al (2018) show that multimodal practices contribute to children’s creation of new contexts through collaborative, communicative and meaning-making experiences, as well as social and co-operative relations. Through digital storytelling, children can organize and express ideas in a personal and meaningful way, be aware of what has captured their interest, as well as provide and explore their points of view about a subject or experience in interaction with the other children and/or their teachers.…”
Section: Theoretical Overviewmentioning
confidence: 96%
“…In the very first years, play is mainly solitary and it has various categories like physical play and drama play (Grammatikopoulos, Gregoriadis, & Zachopoulou, 2012). This type of individualistic play is magnified even more because of the increased screen time children are having due to the covid-19 pandemic, where millions of children are experiencing lockdowns and they have to remain at their houses (Hatzigianni, Gregoriadis, Karagiorgou & Chatzigeorgiadou, 2018). As children grow older, it expands into parallel play, where children play at the same room and they observe each other.…”
Section: Theoretical Backgroundmentioning
confidence: 99%